The Burden of Asthma among South Asian and Chinese Populations Residing in Ontario - Sanja Stanojevic; Baiju R Shah; Sonia S Anand; Malcolm R Sears; Jiandong Su; Padmaja Subbarao (Canadian Respiratory Journal)
BACKGROUND: The South Asian and Chinese populations represent a significant portion of the population of Ontario; however, little is known about the burden of respiratory diseases in these populations.